1997
DOI: 10.1046/j.1365-2427.1997.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of parthenogenesis in the biology of two species of mayfly (Ephemeroptera)

Abstract: 1. From a single founder virgin female of each species, nine and seven successive parthenogenetic generations of Cloeon dipterum and Cloeon simile, respectively, were reared: all offspring were female. Eggs were removed from final instar nymphs, subimagos and virgin imagos of each generation and their development assessed. The life cycles of 487 individual C. dipterum and 315 C. simile were recorded, together with details of growth rate, egg production and adult size of these and other representatives of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Although female parthenogenesis (virgin females laying eggs) has been widely described in some mayfly genera, it is generally thought that entirely female populations are unstable and contribute to an overall reduction in fitness (Funk, Jackson & Sweeney, 2006). Harker (1997) has previously reported that unfertilized eggs take longer and are less probably to hatch in two mayfly species. Although this study did not detect effects on female mayfly emergence patterns or body size for either Baetis or Epeorus, future studies should evaluate egg hatching success.…”
Section: Discussionmentioning
confidence: 99%
“…Although female parthenogenesis (virgin females laying eggs) has been widely described in some mayfly genera, it is generally thought that entirely female populations are unstable and contribute to an overall reduction in fitness (Funk, Jackson & Sweeney, 2006). Harker (1997) has previously reported that unfertilized eggs take longer and are less probably to hatch in two mayfly species. Although this study did not detect effects on female mayfly emergence patterns or body size for either Baetis or Epeorus, future studies should evaluate egg hatching success.…”
Section: Discussionmentioning
confidence: 99%
“…Equally, the term apomixis (apomictic thelytoky) is sometimes used when referring to animals [74] . Thelytoky Hexapoda Odonata Exceptional [34] and Ephemeroptera Very common [35] Deuterotoky Blattoptera Very common [11,36] Mantoptera Very common [11] Isoptera Very common [11] Plecoptera Rare [37] Orthoptera Very common [11] Embioptera Occurs in Oligotomidae [11] Phasmida Very common [11] Psocoptera Less than 4 % [38] Phthiraptera Bovicola sp (Mallophaga) [39] Hemiptera Common, universal in aphids [11,40] Thysanoptera Some species [41] Strepsiptera One possible example [42] Thelytoky and Hexapoda Coleoptera (beetles) 54 Curculionidae, 11 Chrysomelidae, rare in other families [11,40,43] Deuterotoky Hymenoptera Very common [11] Diptera Found in several families [11] Lepidoptera Several Psychidae exceptional elsewhere [40] Echinodermata Asteroidea and Stelleroidea Rare or absent [44] Vertebrata Pisces About eight species (Poeciliidae, Cyprinidae, Atherinidae and Cobitidae) [45] Amphibia About three Ambystoma [45] Reptilia About 36 lizards and two snakes [46][47][48][49][50][51][52][53][54][55] R: Reduced eggs; F: fertilisation of eggs; C: equivalent to clonality. * Except for certain automicts (see Figures 1-3).…”
mentioning
confidence: 99%
“…There are numerous studies on parthenogenesis of other mayflies. Usually, parthenogenesis is suggested or demonstrated via reproductive experiments (Huff and McCafferty 1974;Friesen and Flannagan 1976;Grant and Masteller 1987;Harker 1997;Glazaczow 2001;Funk et al 2006Funk et al , 2010Sekin e et al 2015).…”
Section: Entognathamentioning
confidence: 99%